Efficacy of the seven feature, fifteen point histological scoring system and CD56 in interpretation of liver biopsies in persistent neonatal cholestasis: A five-year study - O H Radhika Krishna; Nadera Sultana; Ramani Malleboyina; A Narendra Kumar; K Ramesh Reddy; Bhuwaneshwar N Rao (Indian Journal of Pathology and Microbiology, 2014)
Context: Neonatal cholestasis (NC) lasting more than 2 weeks affects one in 2500 live births. Extrahepatic biliary atresia (EHBA) and idiopathic neonatal hepatitis account for about 70% of all cases of NC. Differentiating these two conditions is important as patient management is very different for both the conditions. Aims: To assess the usefulness of the seven-feature, 15-point histological scoring system in the interpretation of liver biopsy in NC and usefulness of immunostaining with CD56 (N-CAM) in EHBA. Settings and Design: Retrospective study of 5 years′ duration at a pediatric referral institute, where the case load of NC is high and definitive surgery for EHBA is undertaken after histological confirmation. Materials and Methods: The study is of a 5-year duration conducted between June 2007 and May 2012. A total of 210 cases of NC were clinically diagnosed during this period. All the slides were reviewed with reference to a seven-feature, 15-point histological scoring system assessing its usefulness in the interpretation of liver biopsy in NC and utility of the immunohistochemical marker CD56 was also assessed as an aid in the characterization of bile ductular proliferation in EHBA. Statistical Analysis: Statistical analysis was performed and sensitivity and specificity of the histological scoring system for EHBA was analyzed. Results: Of the 210 liver biopsies reviewed using the scoring system, 122 cases were diagnosed as EHBA and 88 cases were diagnosed as other causes of NC. The overall sensitivity of this scoring system was 95.5%, specificity was 93.1% and diagnostic accuracy was 94.6%. Conclusions: The seven-feature, 15-point histological scoring system has good diagnostic accuracy in the interpretation of liver histology in NC as advanced histopathological findings even at younger age require immediate surgery. CD-56 is a useful marker in the assessment of bile ductular proliferation in EHBA.